BIOGRAPHY OF KH. ACHMAD MUZAKKI SYAH: HIS ROLE AND INFLUENCE IN THE DEVELOPMENT OF AL QODIRI ISLAMIC BOARDING SCHOOL IN JEMBER - Meidiana Putri, Shafira (FAJAR Jurnal Pendidikan Islam, 2025)
This article discusses the biography of KH. Muzakki Syah, a charismatic scholar from Jember, East Java, who is known as the founder of Al-Qodiri Islamic Boarding School. This research aims to explore his life journey, the process of establishing the pesantren, as well as the ideas of da’wah and education that he developed. This research uses historical method with biographical approach. Data were obtained through literature study of scientific articles, biography books, and institutional documentation. The results showed that KH. Muzakki Syah applied Sufistic da’wah with a spiritual therapy approach through dzikir manaqib and multicultural values. Pesantren Al-Qodiri developed into a large foundation with more than 4,000 students and educational institutions from elementary to college level. KH. Muzakki Syah’s contribution reflects the integration of spirituality, local culture, and inclusive education, making his pesantren responsive to socio-religious challenges in the modern era.